Theoretical analysis of a high-performance surface plasmon resonance biosensor using BlueP/WS2 over Cu-Pt bimetallic layer - Myilsamy, Muthumanicam; Cecil Lordwin, Prabhakar; Vibisha, Alagu; Ponnan, Suresh; Zbigniew, Jaroszewicz; Karupiya Balasundaram, Rajesh (Photonics Letters of Poland, 2023)
The present theoretical study exhibits the possibility of achieving extremely high sensitive surface plasmon resonance based biosensor comprising of Cu-Pt bimetallic layer and BlueP/WS2 hybrid nanostructure for angular interrogation method. Based of Transfer matrix method thickness of Cu and Pt as well as the number of BlueP/WS2 layer is optimized to obtain the best possible sensitivity and FOM. The well optimized Cu-Pt-BlueP/WS2 hybridstructure is found to generate sensitivity as high as 502°/RIU with FOM as 128.7RIU-1 such sensor is highly useful for detecting biomolecules. Full Text: PDF References A.H.M. Almawgani, M.G. Daher, S.A. Taya, M. Mashagbeh, I. Colak. "Optical Detection of Fat Concentration in Milk Using MXene-Based Surface Plasmon Resonance Structure", Biosensors 12, 535 (2022). CrossRef E. Kretschmann, H. Raether, "Notizen: Radiative Decay of Non Radiative Surface Plasmons Excited by Light", Z. Naturf. a 23, 2135 (1968). CrossRef M.G. Daher, Y. Trabelsi, Y.K. Prajapati, A. Panda, N.M. Ahmed, A.N.Z. Rashed., "Highly sensitive detection of infected red blood cells (IRBCs) with plasmodium falciparum using surface plasmon resonance (SPR) nanostructure", Opt. Quantum Electron. 55, 199 (2023). CrossRef A.H.M. Almawgani, M.G. Daher, S.A. Taya, M.M. Olaimat, A.R.H. Alhawari, I. Colak., "Detection of Blood Plasma Concentration Theoretically Using SPR-Based Biosensor Employing Black Phosphor Layers and Different Metals", Plasmonics 17,1751 (2022). CrossRef Y. Saad, M. Selmi, M.H. Gazzah, A. Bajahzar, H. Belmabrouk, "Performance enhancement of a copper-based optical fiber SPR sensor by the addition of an oxide layer", Optik 190, 1 (2019). CrossRef N.K. Sharma, S. Shukla, V. Sajal, "Surface plasmon resonance based fiber optic sensor using an additional layer of platinum: A theoretical study", Optik 133, 43 (2017). CrossRef S. Shukla, M. Rani, N.K. Sharma, V. Sajal, "Sensitivity enhancement of a surface plasmon resonance based fiber optic sensor utilizing platinum layer", Optik 126, 4636 (2015). CrossRef S. Singh, A.K. Sharma, P. Lohia, D.K. Dwivedi, "Theoretical analysis of sensitivity enhancement of surface plasmon resonance biosensor with zinc oxide and blue phosphorus/MoS2 heterostructure", Optik 244, 167618 (2021). CrossRef N. Liu, S. Wang, Q. Cheng, B. Pang, J. Lv, "High Sensitivity in Ni-Based SPR Sensor of Blue Phosphorene/Transition Metal Dichalcogenides Hybrid Nanostructure", Plasmonics 16, 1567 (2021). CrossRef S. Shivangani, M.F. Alotaibi, Y. Al-Hadeethi, P. Lohia, S. Singh, D.K. Dwivedi, A. Umar, H.M. Alzayed, H. Algadi, S. Baskoutas, "Numerical Study to Enhance the Sensitivity of a Surface Plasmon Resonance Sensor with BlueP/WS2-Covered Al2O3-Nickel Nanofilms", Nanomater. Basel 12, 2205 (2022). CrossRef M. Yamamoto, "Surface Plasmon Resonance (SPR) Theory: Tutorial", Review of Polarography (JPN) 48, 209 (2002). CrossRef P.K. Maharana, T. Srivastava, R. Jha, "Low index dielectric mediated surface plasmon resonance sensor based on graphene for near infrared measurements", J. Phys. D: Appl. Phys. 47, 385102 (2014). CrossRef S. Pal, N. Pal, Y.K. Prajapati, J.P. Saini, "Sensitivity Analysis of Surface Plasmon Resonance Biosensor Based on Heterostructure of 2D BlueP/MoS2 and MXene", John Wiley & Sons, Inc. 103 (2020). CrossRef S. Singh, A.K. Sharma, P. Lohia, D.K. Dwivedi, "Sensitivity enhancement of SPR biosensor employing heterostructure blue phosphorus/MoS2 and silicon layer", Emerg. Mater. Res. 11, 239 (2022). CrossRef R. Kumar, S. Pal, N. Pal, V. Mishra, Y.K. Prajapati, "High-performance bimetallic surface plasmon resonance biochemical sensor using a black phosphorus–MXene hybrid structure", Appl. Phys. A 127, 1 (2021). CrossRef M. Setareh, H. Kaatuzian, "Sensitivity enhancement of a surface plasmon resonance sensor using Blue Phosphorene/MoS2 hetero-structure and barium titanate", Superlattices Microstruct. 153, 106867 (2021). CrossRef S. Wang, N. Liu, Q. Cheng, B. Pang, J. Lv, "Surface Plasmon Resonance on the Antimonene–Fe2O3–Copper Layer for Optical Attenuated Total Reflection Spectroscopic Application", Plasmonics 16, 559 (2021). CrossRef